Impact of obesity on the prognostic value of the N-terminal pro-B-type natriuretic peptide (NT-proBNP) in patients with acute myocardial infarction. Issue 7 (22nd February 2011) - Lorgis, L; Cottin, Y; Danchin, N; Mock, L; Sicard, P; Buffet, P; L'Huillier, I; Richard, C; Beer, J C; Touzery, C; Gambert, P; Zeller, M; et al.
Abstract : Objective: To examine the influence of obesity on the predictive value of the pro-B-type natriuretic peptide (NT-proBNP) assay in acute myocardial infarction. Design: Prospective observational study. Setting: All intensive care units in one region of France. Patients: 2217 consecutive patients admitted for an acute myocardial infarction matched with respect to age, gender, Killip class and renal function. Main outcome measure: Cardiovascular death at one year. Results: There were three groups (according to body mass index (BMI): obese, overweight and normal) of 739 matched patients. Median levels of NT-proBNP were considerably lower in high BMI patients, by about 20% in overweight and by 60% in obese patients, compared with normal BMI patients. An inverse relationship between the propeptide values and BMI was found in the overall study population (r=−0.20, p<0.0001), and for both genders. In multivariate linear regression, BMI as a continuous variable was a predictor of the log NT-proBNP level, even when adjusted for potential confounders. CV mortality at 1-year follow-up was similar for the three BMI groups (p=0.691). In multivariate logistic regression analysis, log NT-proBNP predicted mortality in normal (OR (95% CI) 3.48 (2.00 to 6.12)) and overweight (OR (95% CI) 3.96 (1.95 to 8.06)) patients, even when adjusted for confounders (GRACE risk score, left ventricular ejection fraction). However, in obese patients, propeptide levels failed to retain their independent prognostic value (OR (95% CI) 1.34 (0.86 to 2.08)). Conclusions: In this large population of patients with myocardial infarction, circulating NT-proBNP levels were considerably lower in obese patients; the significance of the propeptide level as an independent prognostic factor is severely compromised.